Analisis Putusan Peninjauan Kembali Di Bawah Ketentuan Minimum Pidana Penjara Dalam Perkara Narkotika (Studi Kasus Putusan MA Nomor 375 PK/PID.SUS/2024) - Adrian, Sesilia Firsty; Adhitya Widya Kartika (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2025)
The application of law in Indonesia is based on the positive law applicable in Indonesia. There is an application of law in Supreme Court Decision Number 375 PK/Pid.Sus/2024 which is the object of the author's research by reviewing the suitability of the decision by comparing the decision with the positive law applicable in Indonesia. The verdict can be reviewed from formal law by referring to the Criminal Procedure Code as the legal basis, while from material law referring to Law Number 35 of 2009 concerning Narcotics. The application of the law in the Supreme Court Decision is reviewed from formal law by looking at the procedure when the applicant submits a request for a review to reopen a decision that has permanent legal force to be retried in court. The author conducts research on the application of formal law whether it is in accordance with the requirements and procedures contained in the Criminal Procedure Code and in accordance with the process of requesting a Judicial Review. The suitability of the application of material law is also examined by the author reviewing Law Number 35 of 2009 concerning Narcotics and also several related regulations. The purpose of the suitability of the application of law to a decision has an impact on the realization of the pillars of law stated by Gustav Radburch, namely justice, expediency, and legal certainty. The author in this study will examine the realization of the pillar of legal certainty in Supreme Court Decision Number 375 PK/Pid.Sus/2024.